Cruise trouble. A practice-based approach to studying Arctic cruise tourism. (October 2021) - Ren, Carina; James, Laura; Pashkevich, Albina; Hoarau-Heemstra, Hindertje
Abstract: Cruise arrivals in the Arctic often take place in small coastal communities. Although there may be economic benefits for these communities, these are often counterbalanced by social and environmental stresses. In this article, we ask how we can tend to Arctic cruise tourism development using Haraway's concept of staying with the trouble. As a way to bridge often polarized views on cruise tourism as either an economic tool or a destructive force, we propose a practice-based research approach to engage with the complexities of cruise tourism. The aim is to foster response-abililty for Arctic cruise communities to live (better) with cruise tourism. We argue that practice-based approaches help researchers 'stay with the trouble' as it is rooted in everyday experiences and the materiality of cruise destinations. Also, its flat ontology supports a 'tinkering' approach to cruise practices. Highlights: Donna Haraway's concept of staying with the trouble is discussed in the context of Arctic cruise tourism. A practice-based approach to studying the complexity of Arctic cruise tourism is presented. Practice-based 'tinkering' is proposed as a useful approach to the management of Arctic cruise tourism.